Fundamentals of wastewater treatment and engineering - Riffat, Rumana (CRC Press, 2013)
Sustainable Wastewater Treatment and EngineeringIntroduction and historyCurrent practiceEmerging issuesFuture directionsRegulatory requirementsReferencesReaction Kinetics and Chemical ReactorsReaction kineticsHow to find the order of a reactionZero order reactionFirst order reactionSecond order reactionReactorsBatch reactorContinuous-flow stirred tank reactorReactors in seriesSemibatch or semiflow reactorsProblemsReferencesWastewater MicrobiologyIntroductionBacteriaArchaeaProtozoaAlgaeFungiVirusProblemsReferencesNatural Purification ProcessesImpurities in waterDilutionSedimentationMicrobial degradationMeasurement of organic matterDissolved oxygen balanceProblemsReferencesWastewater Treatment FundamentalsIntroductionSources of wastewaterWastewater constituentsWastewater treatment methodsLevels of wastewater treatmentResiduals and biosolids managementFlow diagrams of treatment optionsTypes of biological treatment processesProblemsReferencesPreliminary TreatmentIntroductionScreensShredder/grinderGrit chamberProblemsReferencesPrimary TreatmentIntroductionTypes of settling/sedimentationType I sedimentationType II sedimentationPrimary sedimentationChemically enhanced primary treatmentProblemsReferencesSecondary Treatment: Suspended Growth ProcessesIntroductionMicrobial growth kineticsActivated sludge process (for BOD removal)Modeling suspended growth processesTypes of suspended growth processesStabilization ponds and lagoonsProblemsReferencesSecondary Treatment: Attached Growth and Combined ProcessesIntroductionSystem microbiology and biofilmsImportant media characteristicsLoading ratesStone media trickling filterBiotowerRotating biological contactorHybrid processesCombined processesProblemsReferencesSecondary ClarificationIntroductionSecondary clarifier for attached growth processSecondary clarifier for suspended growth processProblemsReferencesAnaerobic Wastewater TreatmentIntroductionProcess chemistry and microbiologyMethanogenic bacteriaSulfate-reducing bacteriaEnvironmental requirements and toxicityMethane gas productionAnaerobic growth kineticsAnaerobic suspended growth processesAnaerobic attached growth processesHybrid processesProblemsReferencesSolids Processing and DisposalIntroductionCharacteristics of municipal sludgeSludge quantificationSludge thickeningSludge stabilizationConditioning of biosolidsBiosolids dewateringDisposal of biosolidsBiosolids disposal regulations in the United StatesProblemsReferencesAdvanced Treatment ProcessesIntroductionNitrogen removalPhosphorus removalSolids removalProblemsReferencesAppendix Index.